2016
DOI: 10.1111/imm.12562
|View full text |Cite
|
Sign up to set email alerts
|

Transient receptor potential vanilloid 1 expression and function in splenic dendritic cells: a potential role in immune homeostasis

Abstract: SummaryNeuro-immune interactions, particularly those driven by neuropeptides, are increasingly implicated in immune responses. For instance, triggering calcium-channel transient receptor potential vanilloid 1 (TRPV1) on sensory nerves induces the release of calcitonin-gene-related peptide (CGRP), a neuropeptide known to moderate dendritic cell activation and T helper cell type 1 polarization. Despite observations that CGRP is not confined to the nervous system, few studies have addressed the possibility that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 47 publications
1
18
1
Order By: Relevance
“…In addition, the purified CD11c + BMDC population showed significantly lower expression of TRPV1 when compared to the total CD11b + pool, indicating that undifferentiated CD11c − (CD11b + granulocytes) are richer in TRPV1 transcripts. It has been previously reported that TRPV1 is found in a small subpopulation of CD11c + F4/80 − freshly isolated splenocytes and that its expression varies across different mouse strains, the lowest being in C57BL/6J [34], the same background used in our study and elsewhere [33,35]. Thus, a deeper characterization will be required to identify the phenotypic signature of the TRPV1-expressing CD11c + population.…”
Section: Discussionmentioning
confidence: 80%
“…In addition, the purified CD11c + BMDC population showed significantly lower expression of TRPV1 when compared to the total CD11b + pool, indicating that undifferentiated CD11c − (CD11b + granulocytes) are richer in TRPV1 transcripts. It has been previously reported that TRPV1 is found in a small subpopulation of CD11c + F4/80 − freshly isolated splenocytes and that its expression varies across different mouse strains, the lowest being in C57BL/6J [34], the same background used in our study and elsewhere [33,35]. Thus, a deeper characterization will be required to identify the phenotypic signature of the TRPV1-expressing CD11c + population.…”
Section: Discussionmentioning
confidence: 80%
“…Aminoglycosides could be taken up by these DCs via endocytosis 48 or through TRPV family of ion channels 49 which are also expressed on DCs 50 . Aminoglycosides are known for inducing cytotoxicity in specific cell types such as the hair cells of the inner ear and kidney epithelial cells 32,33,36 but their effect on immune cells has not been well characterized.…”
Section: Discussionmentioning
confidence: 99%
“…As an important member of the transient receptor potential family, TRPV1 plays an important role in thermal effect and introduction of pain . TRPV1, however, was reported to be expressed in the aortic arch and participated in the regulation of aortic baroreflex .…”
Section: Discussionmentioning
confidence: 99%